The hunchback of notre dame - Hugo, Victor, 1802-1885 (United Kingdom : Thomson Heinle, 2007)
Set in 15th century Paris, The Hunchback of Notre Dame, centers on gypsy dancer Esmerelda, who is kidnapped and then later rescued from the gallows by hunchbacked bell-ringer Quasimodo
Title from container
Keywords: Paris (France) -- History -- To 1515 -- Fiction; France -- History -- Louis XI, 1461-1483 -- Fiction